Winning a cooperative online vocabulary learning tournament: Teamwork strategies applied by Ecuadorian teachers and students during the COVID-19 pandemic - Cherres Fajardo, Sara Karina; Chumbi Landy, Valeria Alexandra; Morales Jácome, Carmen Elena (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
In foreign language learning contexts, vocabulary acquisition is sometimes perceived as a solitary activity with word lists and flash cards for memorization. However, it is possible to create vocabulary learning tasks that take into account both individual and cooperative efforts in a competitive environment that promotes engagement and motivation. The paper provides an account of the vocabulary learning and teamwork strategies employed by a group of Ecuadorian teachers and students who took part in an international online vocabulary tournament under the unprecedented circumstances of the COVID-19 lockdown in 2020. The data analyzed include reflective vocabulary journals and the WhatsApp messages exchanged. The authors conclude that in addition to the discovery and consolidation strategies for vocabulary learning, the team’s cooperative interactions combined with a high level of social motivation have significantly contributed to their success.